Persepsi Wanita Tani Dalam Program Kawasan Rumah Pangan Lestari (KRPL) Di Kecamatan Kulisusu Kabupaten Buton Utara - Isnian, Sitti Nur; Narti, Narti; Taufik, Yani; Isnan, Sitti Nur (Buletin Penelitian Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Haluoleo, 2019)
This research departs from the phenomenon of the enactment of a Sustainable Food House Area Program (KRPL) policy for food diversification and community nutrition through optimizing women's empowerment. The purpose of this study was to determine the perceptions of women farmers in the KRPL Program. This research was conducted in Jampaka Village, Kulisusu Subdistrict, North Buton Regency, which was selected purposively which was conducted in January-February 2018. This study involved female farmers who were involved in the KRPL Program. The population in this study were all female farmers involved in the KRPL Program totaling 20 people, the sampling was done by census method so that the entire population became respondents. This study was designed as a quantitative study using a percentage formula which then data is presented in table form, to be interpreted qualitatively. The results of this study indicate that the perceptions of women farmers in the KRPL Program in Jampaka Village, Kulisusu Subdistrict, North Buton Regency are of high category, which is due to the age of the adult category, high farming experience, moderate family dependence, and mentoring assistance from the time of socialization to program implementation.